2004
DOI: 10.1292/jvms.66.1219
|View full text |Cite
|
Sign up to set email alerts
|

Glutathion Peroxidase and Glucose-6-Phosphate Dehydrogenase Activities in Bovine Blood and Liver

Abstract: ABSTRACT. A total of 46 cattle, including 25 as control, 16 with glycogen degeneration and 5 with severe fatty degeneration were studied. Whole blood and liver tissue specimens were used to measure glutathione peroxidase (GSH-Px) and Glucose-6-Phosphate Dehydrogenase (G6PD) activities. The present study determined the value of these parameters in diagnosing glycogen and fatty degeneration in cattle from the point of the status of antioxidation and lipid peroxidation. The results showed a significant decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
0
24
0
2
Order By: Relevance
“…The enzyme uses glutathione as the ultimate electron donor to regenerate the reduced form of the selenocysteine. [10]…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme uses glutathione as the ultimate electron donor to regenerate the reduced form of the selenocysteine. [10]…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the changes in the hepatic total glutathione level and glutathione reductase activity may be attributed to a combination of hepatic dysfunction and the effect of ethionine. The absence of oxidative stress in natural cases of hepatic glycogen degeneration [3] indicated that the effect on hepatic antioxidant parameters in the current study may be attributed to ethionine. Ethionine was reported to affect the glutathione metabolism in rat liver a short period after injection, which varied from 4 hr [25] to 24 hr [10] followed by significant increase in 2 days [19] or 3 days [24].…”
mentioning
confidence: 52%
“…Cellular glutathione and related enzymes such as glutathione peroxidase, glutathione S-transferase and glutathione reductase are among the principal protective mechanisms against endogenous and exogenous toxic substances and free radicals-mediated damage in liver tissue as well as in other tissues [5,8,9,13,14]. Increased oxidative stress in bovine liver diseases was established in fatty liver [3] and liver abscesses [2]. In addition, underfeeding in cattle was reported to induce changes in the antioxidant systems in the liver [16].…”
mentioning
confidence: 99%
“…A second major function of pentose phosphate pathway is to generate essential pentoses, particularly D-ribose used in the biosynthesis of nucleic acids. In bovines, G6PD activity increases significantly in cases of fatty degeneration indicating an increase in lipoperoxidation process in liver tissue (Abd Ellah et al 2004) and under oxidative stress in cattle infected with Theileria annulata (Grewal et al 2005). In in vitro produced bovine blastocysts, inhibition of X-linked gene product G6PD normalizes the sex ratio from skewing towards females (Kimura et al 2005).…”
Section: Introductionmentioning
confidence: 99%